A COMPARATIVE STUDY OF ILLNESS PERCEPTION, ILLNESS ANXIETY, COPING STRATEGIES AND SOCIAL SUPPORT AMONG ACTIVE CANCER PATIENTS AND POST-TREATMENT SURVIVORS (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Cancer diagnosis and treatment are often associated with significant psychological distress that may affect emotional well-being. Psychological factors such as illness perception, illness anxiety, coping strategies, and perceived social support influence individuals’ adjustment to illness. Aim: To compare illness perception, illness anxiety, coping strategies, and perceived social support among active cancer patients and post-treatment survivors. Materials and Methods: A comparative cross-sectional study was conducted among 64 participants (32 active cancer patients and 32 post-treatment survivors) aged 18–65 years recruited from oncology departments of a tertiary care hospital. Psychological variables were assessed using the Illness Perception Questionnaire (IPQ), Health Anxiety Inventory (HAI-18), Brief COPE, and the Multidimensional Scale of Perceived Social Support (MSPSS). Data were analyzed using descriptive statistics, independent t-tests, and regression analysis. Results: Active cancer patients reported higher illness anxiety and more negative illness perceptions compared to survivors. Post-treatment survivors demonstrated better coping strategies and higher perceived social support. Illness perception and social support positively predicted emotional well-being, whereas illness anxiety negatively predicted emotional well-being. Conclusion: The findings indicate psychological differences between active cancer patients and post-treatment survivors, highlighting the importance of stage-specific psychosocial interventions.